Novelty Elements and Changes Brought to Adoption Procedure by Law No. 57/2016 (Journal of Legal Studies, 2017)
Adoption is chief among the measures of alternative protection that can be taken to protect a child in Romania. According to Law no. 273/2004 on adoption procedure, current forms under which adoption can be found are domestic adoption and international adoption. In what follows we will highlight certain novelty elements and changes to the domestic adoption procedure brought by Law no. 57/2016.